Determinasi Pertumbuhan Ekonomi Regional melalui Indikator Pembangunan Gender: Studi Data Panel Kabupaten/Kota se-Provinsi Kalimantan Selatan Periode 2019-2023 - Bulqis Nahlia; Chairul Sa'roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This research paper aims to examine the impact of gender development on the growth of Gross Regional Domestic Product (GDP) in South Kalimantan Province from 2019 to 2023 using the Gender-Based Ratio approach. The method used is panel data regression analysis with a Random Effect Model (REM). Secondary data used covers 13 districts and cities and was analyzed using Eviews 12 software. The results of the study indicate that, collectively, the life expectancy ratio, the expected years of schooling ratio, and the labor force participation rate ratio significantly influence the growth of Gross Regional Domestic Product (GRDP). Separately, life expectancy, expected years of schooling ratio, and the labor force participation rate show significant effects, while per capita expenditure does not show a substantial influence. The most dominant factor identified is life expectancy. These results indicate that improving the quality of health and education is crucial for driving economic growth. Consequently, there is a need for more inclusive and gender-focused development policies to ensure sustainable and equitable economic growth across the region.